Прогресивні підходи у вдосконаленні технології виготовлення тришарошкових бурових доліт - Яким, Роман; Петрина, Юрій; Яким, Ігор (КІНПАТРІ ЛТД, 2013)
The complex approach to the improvement of three-cone rock bits manufacturing method, that includes the requirements increase for the chemical composition of rock bit steels, and also the advanced approaches to the improvement of technological processes quality and efficiency are offered.
Advanced approaches to the improving of three-cone rock bits manufacturing method